2009
DOI: 10.1007/s00270-009-9691-7
|View full text |Cite
|
Sign up to set email alerts
|

Technique, Complication, and Long-Term Outcome for Endovascular Treatment of Iliac Artery Occlusion

Abstract: The aim of this study was to report technical details, procedure-related complications, and results of endovascular treatment in chronic iliac artery occlusion. Between 2001 and 2008, endovascular treatments of 127 chronic iliac artery occlusions in 118 patients (8 women and 110 men; mean age, 59 years) were retrospectively reviewed. The study was based on Ad Hoc Committee on Reporting Standards (Society for Vascular Surgery/International Society for Cardiovascular Surgery Standards). All occlusions were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 16 publications
1
55
0
4
Order By: Relevance
“…Several intraoperative and immediate complications were recorded, however, with a threefold increased risk of complications in group 1 that only approached significance, probably due to the low number of cases (type II statistical error). Similarly, Ozkan et al 16 reported in their large series concerning early and late results of endovascular treatment of chronic iliac occlusion a complication rate of 19%, successfully treated in most cases with an endovascular procedure. A pooled analysis of 38 studies of iliac PTA and of 18 studies of stenting 2 reported a complication rate of 2.7% and 6%, respectively; however, the results were not separately analyzed between stenoses and occlusions.…”
Section: Discussionmentioning
confidence: 91%
“…Several intraoperative and immediate complications were recorded, however, with a threefold increased risk of complications in group 1 that only approached significance, probably due to the low number of cases (type II statistical error). Similarly, Ozkan et al 16 reported in their large series concerning early and late results of endovascular treatment of chronic iliac occlusion a complication rate of 19%, successfully treated in most cases with an endovascular procedure. A pooled analysis of 38 studies of iliac PTA and of 18 studies of stenting 2 reported a complication rate of 2.7% and 6%, respectively; however, the results were not separately analyzed between stenoses and occlusions.…”
Section: Discussionmentioning
confidence: 91%
“…2,7,10,11 Most of these series utilize intraluminal techniques to traverse the iliac obstruction, with a minority of lesions managed with SIA. In this study of iliac artery CTO managed exclusively with SIA, 34.7% of the lesions were graded TASC D. Although a technical success rate of 83.5% was seen in this study, the majority of these lesions were TASC C and D (61.4%), and all of these lesions were iliac artery CTOs.…”
Section: Discussionmentioning
confidence: 98%
“…Heavy calcification and a retrograde femoral approach are risk factors for technical failure. 8 Furthermore, retrograde attempts typically require the use of expensive re-entry devices that are associated with significant costs 9 but still do not guarantee technical success. 4,8 The technique we have described here is simple but valuable in increasing technical success.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, retrograde attempts typically require the use of expensive re-entry devices that are associated with significant costs 9 but still do not guarantee technical success. 4,8 The technique we have described here is simple but valuable in increasing technical success. We believe approaching these lesions by starting at the proximal cap of the iliac occlusion can increase the technical success rate because it is easier to regain true lumen access from this antegrade approach.…”
Section: Discussionmentioning
confidence: 99%